Timing and Outcomes of Intracranial Stenting in the Post-SAMMPRIS Era: A Systematic Review - Yu, Yanying; Wang, Tao; Yang, Kun; Zhang, Xiao; Yu, Simon Chun Ho; Luo, Jichang; Yang, Bin; Wang, Yabing; Ma, Yan; Gao, Peng; Jiao, Liqun (Frontiers in Neurology, 2021)
Objective: To investigate the impact of timing on the safety and efficacy of stenting for ICAS, we reviewed high-volume randomized controlled trials or prospective cohort studies of stenting for intracranial atherosclerotic artery stenosis (ICAS) after the SAMMPRIS trial. Methods: We included randomized controlled trials or prospective cohort studies since 2011 (the publication of the SAMMPRIS trial), evaluating the outcomes of intracranial stenting for ICAS patients. The primary outcomes were perioperative and 1-year stroke or death rate. The interaction of timing and outcomes were shown on trend plots. Overall meta-analysis and subgroup analysis by timing of intracranial stenting were conducted. Results: Fourteen studies with a total of 1950 patients were included. The perioperative and post-operative stroke or death rates decreased with the time of stenting to the qualifying events. The perioperative stroke rate was significantly higher in patients treated within 21 days after the qualifying events, compared to those beyond 21 days (IRR 1.60, 95%CI 1.10-2.33; p = 0.014), similar relationships were obtained for both post-procedural (IRR 1.61, 95%CI 1.02-2.55; p = 0.042) and 1-year (IRR 1.51, 95%CI 1.10-2.08; p = 0.012) stroke or death rate. Conclusions: The timing of intracranial stenting may influence the safety and efficacy outcomes of stenting. Intracranial stenting within 21 days from the qualifying events may confer a higher risk of stroke or death. More studies are needed to confirm the impact of timing and the proper cut-off value.